Integrating non-renewable energy consumption, geopolitical risks, economic development with the ecological intensity of wellbeing: evidence from quantile regression analysis - Khurshid, Nabila; Egbe, Chinyere Emmanuel; Akram, Nabila (Frontiers in Energy Research, 2024)
Introduction: This study delves into the intricate relationship between non-renewable energy sources, economic advancement, and the ecological footprint of well-being in Pakistan, spanning the years from 1980 to 2021. Methods: Employing the quantile regression model, we analyzed the co-integrating dynamics among the variables under scrutiny. Non-renewable energy sources were dissected into four distinct components—namely, gas, electricity, and oil consumption—facilitating a granular examination of their impacts. Results and discussion: Our empirical investigations reveal that coal, gas, and electricity consumption exhibit a negative correlation with the ecological footprint of well-being. Conversely, coal consumption and overall energy consumption show a positive association with the ecological footprint of well-being. Additionally, the study underscores the detrimental impact of geopolitical risks on the ecological footprint of well-being. Our findings align with the Environmental Kuznets Curve (EKC) hypothesis, positing that environmental degradation initially surges with economic development, subsequently declining as a nation progresses economically. Consequently, our research advocates for Pakistan’s imperative to prioritize the adoption of renewable energy sources as it traverses its developmental trajectory. This strategic pivot towards renewables, encompassing hydroelectric, wind, and solar energy, not only seeks to curtail environmental degradation but also endeavors to foster a cleaner and safer ecological milieu.